Dipolar molecules inside C70: an electric field-driven room-temperature single-molecule switch. Issue 48 (28th November 2016) - Foroutan-Nejad, Cina; Andrushchenko, Valery; Straka, Michal
Abstract : A dipolar molecule enclosed inside C70 works as a single-molecule switch driven by an external electric field. Abstract : We propose a two-state electric field-driven room-temperature single-molecule switch based on a dipolar molecule enclosed inside ellipsoidal fullerene C70 . We show that the two low-energy minima of the molecular dipole inside the C70 cage provide distinguishable molecular states of the system that can be switched by application of an external electric field.